Representation of Moral Values in Song of Madurese Children's Games - Agus Salimullah; Hasan Busri; Akhmad Tabrani (EDUTEC : Journal of Education And Technology, 2023)
This research aims to obtain an objective description of the representation of moral values contained in the verses of Madurese children's game songs. The moral values include individual moral values, social moral values, and religious moral values. This research is a descriptive qualitative research. Madurese children's game songs became the data source of this research, while the data were taken from phrases or clauses in the Madurese children's game songs. Based on the results of this study, the author found three aspects of moral values of human life contained in the lyrics of Madurese children's game songs, namely human relationships with God (religious), human relationships with themselves (individual), and human relationships with other humans (social). In more detail, the relationship pattern consists of: Moral Values about the Individual which consists of, (1) the principle of honest living, (2) self-love, and (3) the spirit of hard work. Moral Values about Social consists of, (1) mutual cooperation attitude, (2) love and respect for others, and Moral Values about Religion which consists of, (1) the value of obedience in carrying out religious / God's provisions, (2) praiseworthy values, humble and spacious, and (3) the value of ripples of personal conscience.